Aligning domestic policies with international coordination in a post-Paris global climate regime: A case for China - Li, Jun; Hamdi-Cherif, M.; Cassen, C. (Elsevier Inc., 2017)
© 2017 Elsevier Inc. The Paris COP-21 reached a climate agreement on 2-degree global emissions stabilisation target. However, the likelihood of successfully implementing a legally binding global climate treaty will depend to a large degree on the macroeconomic impacts of different policy options on developing and emerging economies. It is thus crucial to evaluate the transition costs of implementing different climate policy architectures under socioeconomic and technological uncertainties from a multiregional perspective. Here we use a hybrid computable general equilibrium model, in which sub-optimalities, infrastructural inertia and technological uncertainties are explicitly introduced, to quantify the trajectories of variation in transitions costs under a range of climate policy scenarios in both Annex I and developing nations. The policy architectures are based around the implementation of the 'streamlined Paris Pledges' (SPP) in developing countries with a particular focus on China and India. Our results indicate that the distributional effects should be taken into account by policymakers through extension of SPP to 2050 as global climate policies may have asymmetrical economic impacts between Annex I and developing countries. A first-best policy of global cap-and-trade scheme alone could be welfare-deteriorating for some parties, reflected by a significant reduction in macroeconomic growth rate over the course of the next decades. Modelling results also suggest that articulating both global and national policies in a multiregional climate deal can provide a palatable solution for countries like China as this would allow for significant reduction in the economic losses associated with a unique-carbon-price global climate policy. This hybrid approach is also aligned with specific development priorities in developing and emerging countries by providing flexibility to their domestic policy framework, which expects to facilitate the transition to low carbon growth trajectory by encouraging intersectoral coordination. Last, procrastination of technical change and delayed structural reform for decarbonising economy would entail significantly higher transition costs for developing countries in case of stringent climate policy due to the economic competitiveness forgone as a result of exorbitant carbon prices in the longer term. Relevant policy options and research perspectives are discussed accordingly.